Method for Lightweight Optimization for Aerospace Milled Parts – Case Study for a Helicopter Pilot Lightweight Crashworthy Seat Side Struts. (2015) - Dima, Gabriel; Balcu, Ion; Zamfir, Mircea
Abstract: As a follow up of the light weight design policies, topology optimization of aerospace milled parts is on the focus of development teams from many years. In the last period (especially after Airbus A380 roll up) there were presented methods to save weight and even parts on airplanes manufactured this way. Emerged form an aerospace structures design team, paper presents a method to combine the 2D topological optimization with classic 3D static stress design iterations, leading to significant weight savings. The results will be implemented on a future helicopter operator seat under development for a multirole helicopter.